2007
DOI: 10.1111/j.1540-4781.2007.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Firth and Wagner (1997): New Ideas or a New Articulation?

Abstract: This article begins with a review of second language acquisition research leading up to the 1997 article by Firth and Wagner. We argue that the Firth and Wagner article did not represent a new direction, but rather continued a type of argumentation that was already prevalent in the field at the time of the 1997 publication. We identify 3 issues as key in Firth and Wagner's argument: the scope of the research question, the multiple identities of research participants, and the context considered in research. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Cook envisioned the different languages that a person speaks as one connected system in which the languages influence one another, rather than as discrete systems in which the second language or foreign language is in isolation from the first or subsequent languages. To better capture contextual and dimensional aspects of language use, Firth and Wagner (1997) suggested that researchers use emic approaches that address individuals' personas in more complete ways and highlight the identities that are most relevant to the setting (Block, 2007;Gass, Lee, & Roots, 2007;Lafford, 2007). Kramsch also suggested a departure from the view of the student of foreign languages as merely a learner of the TL, instead depicting the individual as a multilingual subject (Kramsch, 2006b(Kramsch, , 2009(Kramsch, , 2010Kramsch & Gerhards, 2012) who is created and shaped by language use.…”
Section: Multiple Languages Multiple Identitiesmentioning
confidence: 99%
“…Cook envisioned the different languages that a person speaks as one connected system in which the languages influence one another, rather than as discrete systems in which the second language or foreign language is in isolation from the first or subsequent languages. To better capture contextual and dimensional aspects of language use, Firth and Wagner (1997) suggested that researchers use emic approaches that address individuals' personas in more complete ways and highlight the identities that are most relevant to the setting (Block, 2007;Gass, Lee, & Roots, 2007;Lafford, 2007). Kramsch also suggested a departure from the view of the student of foreign languages as merely a learner of the TL, instead depicting the individual as a multilingual subject (Kramsch, 2006b(Kramsch, , 2009(Kramsch, , 2010Kramsch & Gerhards, 2012) who is created and shaped by language use.…”
Section: Multiple Languages Multiple Identitiesmentioning
confidence: 99%
“…That is, these initial reactions tell us very little of how the acceptance or rejection of the text's propositions change diachronically. For example, Firth and Wagner's SLA-focused article (1997) initially incited controversy and "angered" several SLA scholars (Gass, Lee, & Roots, 2007). Their article, however, has over time "crystalized the essence of many of these polemical cognitive-social arguments and provided valuable insights into the perspectives underlying current avenues of SLA research" (Lafford, 2007, p. 744).…”
Section: Reception Studiesmentioning
confidence: 99%